Cover note - Standing Joint Committee of Industrial Women's Organisations. Spanish Relief Committee
1939-05-26 001-0008-001 T.U.C. International Dept I understand someone asked for figures, which will be found in this minute. M.E.S. 26/5/39 292/946/1/8(i)